Compressive strength of cement stabilized cold in-place recycling pavement base course with ground coal bottom ash and calcium chloride - Mohd Izzat Joohari; Ekarizan Shaffie; Anas Ibrahim; Mohd Tarmizi Che Othman (Penerbit Universiti Kebangsaan Malaysia, 2024)
Pavement degradation throughout its design life requires rehabilitation to maintain its functionality. Conventional repair methods, such as ‘remove and replace,’ are costly and environmentally unfriendly. Cold in-place recycling (CIPR) has emerged as an eco-friendly alternative for addressing severe pavement damage. CIPR involves recycling the existing pavement and part of the base layer, which are then compacted to form a new base layer with the addition of a stabilizing agent. In Malaysia, cement is a commonly used stabilizing agent. However, the extensive use of cement raises environmental concerns, as its production contributes between 5-9% of global CO2 emissions. This study explores partially replacing ordinary Portland cement (OPC) with ground coal bottom ash (GCBA) and using calcium chloride (CaCl₂) as an accelerator to address this issue. The study varied OPC content from 1-4%, with GCBA and CaCl₂ ranging from 0-3%. An unconfined compressive strength (UCS) test was conducted to analyze the effects on compressive strength and strength development over time. Results indicated that the optimal GCBA percentage for cement replacement is 1%, while the optimal CaCl₂ content is between 1% and 2%. Overall, compressive strength increased with curing time, highlighting the potential of this innovative approach to pavement rehabilitation.